Model Pembiayaan Syariah untuk Sektor Pertanian - Zubaidah Nasution (Institut Agama Islam Negeri Madura, 2016)
Agriculture sector has a very strategic role international development. One of the main problems in agriculture development is the weaknesses of capital support. Shariah banks, have a significant potential for agricultural financing because of core business as the financial intermediary institution. However, the facts showed that Shariah banking financing to agriculture sector is still limited that it less than 4 %. This paper aims to review potential of Shariah banks and examines financing for capital support in agriculture sector. The method which are used in this paper are correlational and descriptive qualitative, with secondary data. The findings of this study will reflect the true picture of financing agriculture sector with formulating an alternative financing scheme in accordance with the characteristics of agriculture based on Shariah perspective. It might be beneficial for the existing Islamic banks to enhanced their performance in agricultural financing.